Tunable physical properties in Bi-based layered supercell multiferroics embedded with Au nanoparticles. Issue 14 (21st June 2022) - Shen, Jianan; He, Zihao; Zhang, Di; Lu, Ping; Deitz, Julia; Shang, Zhongxia; Kalaswad, Matias; Wang, Haohan; Xu, Xiaoshan; Wang, Haiyan
Abstract : An Aurivillius-phase multiferroic material Bi1.25 AlMnO3.25 embedded with Au NPs displays tunable functionalities at various deposition temperatures. Abstract : Multiferroic materials are an interesting functional material family combining two ferroic orderings, e.g., ferroelectric and ferromagnetic orderings, or ferroelectric and antiferromagnetic orderings, and find various device applications, such as spintronics, multiferroic tunnel junctions, etc. Coupling multiferroic materials with plasmonic nanostructures offers great potential for optical-based switching in these devices. Here, we report a novel nanocomposite system consisting of layered Bi1.25 AlMnO3.25 (BAMO) as a multiferroic matrix and well dispersed plasmonic Au nanoparticles (NPs) and demonstrate that the Au nanoparticle morphology and the nanocomposite properties can be effectively tuned. Specifically, the Au particle size can be tuned from 6.82 nm to 31.59 nm and the 6.82 nm one presents the optimum ferroelectric and ferromagnetic properties and plasmonic properties. Besides the room temperature multiferroic properties, the BAMO-Au nanocomposite system presents other unique functionalities including localized surface plasmon resonance (LSPR), hyperbolicity in the visible region, and magneto-optical coupling, which can all be effectively tailored through morphology tuning. This study demonstrates the feasibility of coupling single phase multiferroic oxides with plasmonic metals for complex nanocomposite designs towards optically switchable spintronics and other memory devices.